How best to assess right ventricular function by echocardiography*. (December 2015) - DiLorenzo, Michael P.; Bhatt, Shivani M.; Mercer-Rosa, Laura
Abstract: Right ventricular function is a crucial determinant of long-term outcomes of children with heart disease. Quantification of right ventricular systolic and diastolic performance by echocardiography is of paramount importance, given the prevalence of children with heart disease, particularly those with involvement of the right heart, such as single or systemic right ventricles, tetralogy of Fallot, and pulmonary arterial hypertension. Identification of poor right ventricular performance can provide an opportunity to intervene. In this review, we will go through the different systolic and diastolic indices, as well as their application in practice. Quantification of right ventricular function is possible and should be routinely performed using a combination of different measures, taking into account each disease state. Quantification is extremely useful for individual patient follow-up. Laboratories should continue to strive to optimise reproducibility through quality improvement and quality assurance efforts in addition to investing in technology and training for new, promising techniques, such as three-dimensional echocardiography.